The concept of "Principles of spiritual development" and its sociophilosophical analysis - Makhmut Mamatov (Genius Journals, 2023)
In the formation of the concept of "Principles of spiritual development", social, economic and political factors along with the events that take place in the spiritual and educational aspects, various processes related to them are important in educational practice. In this article, information about the embodiment of the human essence, its value as a being through spiritual values, that spirituality is a concept that represents the spiritual and me ntal world of a person, and that it includes the philosophical, legal, scientific, artistic, moral, imaginations of people.
Keywords: concept; law; action; principle